PHILOSOPHICAL IMPORTANCE OF YAGYA - Khari, Neetanjali (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The word Yagya is derived from Sanskrit root ‘Yaj’ with suffix ‘Nad’, which literally means worship of God, association and charity.1 This etymological meaning proves that the act by which inanimate and conscious Gods, inanimate objects and things are donated is called Yagya. The act by which the desired thing is achieved, the desire is fulfilled is the same act. On the basis of Maharishi Panini’s explanation of Yagya, Pandit Budhdev Vidyalankar has defined Yagya and written that – the works done for the welfare of the community by becoming a part of the community are called Yagya.2 The commentator of Amarakosha has given the etymological meaning of the word Yagya that the Yagya which is performed, the means by which Yagya is performed is Yagya.